A Study on Consumer Behaviour towards Branded Sunglasses amongst the Students of Indore City - Jain, P; Ubeja, S; Tiwari, V (International Journal of Computer Sciences and Engineering, 2025)
We have seen lots of study revealing that marketers are focusing more and more on branding of the product. They believe in the fact that a product when become brand easily persuades customers towards the ultimate product. Branding decisions does not work in isolation. Integrated marketing communication has a deep impact in the mind of customers while selecting a branded product. The Present study investigates consumer behaviour towards branded sunglasses and to ascertain the brand of sunglasses most preferred by students of Indore city. In this primary data is collected with the help of structured questionnaire based on scale proposed by Strizhakova, Couter and Price (2008) administered to 130 student’s respondents in Indore city. The secondary information has been collected from the several published sources such as Journals, e- newspapers and websites. These were helpful for interpretation of the primary data into a sequential order and put them in a systematic way to get the desired output. This study is focused on understanding the perception of customer in the selection of sunglasses for personal purposes with special reference to brand consciousness and to identify the factors that are influencing customerbuying decisions of branded sunglasses. The present study has tested the hypothesis to find a significant difference in the opinion of respondents on the brand selection in respect of their demographic factors. Because of the study, it has been identified that quality, and social association plays a significant role in affecting the brand selection of sunglasses where price has very little effect. This study is useful for researchers who want to conduct further studies in the related field of study and the outcome will help industry people to understand the consumer behaviour for better future prospects